Error aversion or management? Exploring the impact of culture at the sharp-end of production in a mega-project. (May 2022) - Matthews, Jane; Love, Peter E.D.; Ika, Lavagnon A.; Fang, Weili
Abstract: The research we present in this paper addresses the following question: What type of error culture does the rank-and-file workforce experience during construction, and does it help mitigate rework? We undertake an exploratory case study of an Alliance, which forms part of a transport mega-project. An error culture questionnaire is administered to the Alliance's subcontractors' workforce across four projects. We find that an error management culture positively correlates with reductions in rework and holds a divergent relationship with an error aversion culture. We further reveal a negative association between an error aversion culture and the ability to reduce rework. Consequently, we question the contemporary wisdom that assumes that error prevention should be combined with error management to create an adaptive culture, aiming to minimise the negative and maximise positive error consequences. We finally discuss the study's limitations and implications for future research examining error culture in construction projects. Highlights: Limited knowledge exists about error culture in construction projects. An exploratory study of a subcontractors perceptions of an alliance's error is examined. An error culture questionnaire is administered to subcontractors of an alliance. An error management culture positively correlates with reductions in rework. The combining of error prevention with error management to create an adaptive culture is questioned.